A noncatalytic domain conserved among cytoplasmic protein-tyrosine kinases modifies the kinase function and transforming activity of Fujinami sarcoma virus P130gag-fps. - Sadowski, I (1986)
Proteins encoded by oncogenes such as v-fps/fes, v-src, v-yes, v-abl, and v-fgr are cytoplasmic protein tyrosine kinases which, unlike transmembrane receptors, are localized to the inside of the cell. These proteins possess two contiguous regions of sequence identity: a C-terminal catalytic domain of 260 residues with homology to other tyrosine-specific and serine-threonine-specific protein kinases, and a unique domain of approximately 100 residues which is located N terminal to the kinase region and is absent from kinases that span the plasma membrane. In-frame linker insertion mutations in Fujinami avian sarcoma virus which introduced dipeptide insertions into the most stringently conserved segment of this N-terminal domain in P130gag-fps impaired the ability of Fujinami avian sarcoma virus to transform rat-2 cells. The P130gag-fps proteins encoded by these transformation-defective mutants were deficient in protein-tyrosine kinase activity in rat cells. However v-fps polypeptides derived from the mutant Fujinami avian sarcoma virus genomes and expressed in Escherichia coli as trpE-v-fps fusion proteins displayed essentially wild-type enzymatic activity, even though they contained the mutated sites. Deletion of the N-terminal domain from wild-type and mutant v-fps bacterial proteins had little effect on autophosphorylating activity. The conserved N-terminal domain of P130gag-fps is therefore not required for catalytic activity, but can profoundly influence the adjacent kinase region. The presence of this noncatalytic domain in all known cytoplasmic tyrosine kinases of higher and lower eucaryotes argues for an important biological function. The relative inactivity of the mutant proteins in rat-2 cells compared with bacteria suggests that the noncatalytic domain may direct specific interactions of the enzymatic region with cellular components that regulate or mediate tyrosine kinase function.